Menelaah Proses Pelaksanaan Program Literasi Pada SDN 024 Tarai Bangun, SDN 037 Karya Indah, SDN 017 Pandau Jaya Dan SDIT Azzuhra Kab. Kampar - Annisa Rahma Aulia; Anzelina Putri; Nila Alfiatunnikmah; Tenesya Dara Saski; Febrina Dafit (Lembaga Pengembangan Kinerja Dosen, 2023)
Referring to the Big Indonesian Dictionary (KBBI), Literacy is the ability to write and read. And based on the Regulation of the Minister of Education and Culture number 23 of 2015, the School Literacy Movement (GLS) strengthens the moral development movement. The School Literacy Movement (GLS), which has been launched by the government, aims to increase interest in reading and familiarize students with reading routines. This research was conducted by the author in order to find out how the process and implementation of literacy programs in several elementary schools in Pekanbaru City and Kampar Regency. Regarding the elementary schools that were used as research objects, namely SDN 024 Tarai Bangun, SDN 037 Karya Indah, SDN 017 Pandau Jaya, and SDIT Az-zuhra. Which of the literacy implementation programs that we observed included Reading-Writing Literacy, Numeracy. Science Literacy, Cultural and Citizenship Literacy, Financial Literacy, and Digital Literacy. By conducting interviews and observations as the method used. The results of this study are intended to add insight regarding the successful implementation of literacy programs, challenges and suggestions.